Makna Eksistensi Manusia sebagai Khalifah: Telaah Filosofis atas Simbolisme “The Creation of Adam” dalam Perspektif Islam - Syarhabil Ali Fikri (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren, 2026)
This study aims to analyze the meaning of human existence as a caliph through a philosophical study of the symbolism of Michelangelo's painting The Creation of Adam from an Islamic perspective. The painting depicts the moment of giving life to Adam through a symbolic touch between God and humans. In Islam, the concept of Adam's creation not only shows the origin of humans, but also emphasizes the position of humans as caliphs on earth as explained in the Qur'an Surah Al-Baqarah verse 30. The method used is library research with a philosophical and hermeneutic approach. The results of the study show that the symbolism in the painting can be interpreted as a representation of the ontological relationship between humans and God, although there are fundamental differences with the Islamic concept of monotheism which does not allow the visualization of God. The Islamic perspective views human existence not only as a biological creature, but as a caliph who has moral, spiritual, and social responsibilities in managing life on earth.